2015
DOI: 10.18632/oncotarget.4924
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer-derived exosomes transfer miRNAs to dendritic cells and inhibit RFXAP expression via miR-212-3p

Abstract: It has been reported tumor-derived exosomes can transfer miRNAs to recipient cells in the tumor microenvironment, promoting tumor invasion and metastasis. The present research aimed to explore how pancreatic cancer (PC) derived exosomal miRNAs inhibited mRNA expression of dendritic cells and induced immune tolerance. Our study revealed that 9 PC-related miRNAs were increased and 208 mRNAs were inhibited in exosome-stimulated dendritic cells (exo-iDCs) compared to immature dendritic cells (iDCs). A target predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(187 citation statements)
references
References 31 publications
3
170
0
2
Order By: Relevance
“…A previous study demonstrated miR-212-3p involved in the generation of pancreatic cancer-derived exosomes and could suppress RFXAP protein expression in DCs and thus elicit DC immune tolerance (8). Other studies have also demonstrated the key function of miR-212-3p in pancreatic cancer metastasis; Park et al (22) demonstrated that miR-212 expression increased in pancreatic cancer cells and promoted their proliferation by inhibiting Retinoblastoma 1 gene expression in a targeted manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated miR-212-3p involved in the generation of pancreatic cancer-derived exosomes and could suppress RFXAP protein expression in DCs and thus elicit DC immune tolerance (8). Other studies have also demonstrated the key function of miR-212-3p in pancreatic cancer metastasis; Park et al (22) demonstrated that miR-212 expression increased in pancreatic cancer cells and promoted their proliferation by inhibiting Retinoblastoma 1 gene expression in a targeted manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that regulatory factor X-associated protein (RFXAP) is a key transcription factor for the synthesis of MHC class II molecules in dendritic cells (DCs) (7). Exosomal microRNA (miRNA/miR)-212-3p secreted by pancreatic cancer cells can inhibit RFXAP expression in DCs, and thus suppress MHC class II expression and promote the immune escape of pancreatic tumors (8). This may explain why MHC class II expression is downregulated in pancreatic cancer, which leads to poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal microRNA such as miR-212-3p, miR-203, miR-21 have been shown to enhance invasion, modulate immune response and drug resistance (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ding G et al showed that pancreatic cancer-derived exosomal miR-212-3p inhibits the expression of regulatory factor X-associated protein (RFXAP), a key transcription factor for major histocompatibility complex II (MHC II) in DCs. RFXAP inhibition results in decreased MHC II expression and inactivation of CD4 + T-lymphocytes, ultimately inducing immune tolerance [35]. These data describe a novel mechanism of pancreatic cancer immune tolerance, and suggest that eliminating cancer-derived exosomes can act as an immune agonist in pancreatic cancer immunotherapy.…”
Section: To Help Pancreatic Cancer Cells Escape Immune Responsesmentioning
confidence: 77%